Pelatihan Bahasa Indonesia Bagi Penutur Asing (BIPA) di Fakultas Liberal Arts,Universitas Maejo, Thailand - Wiyanti, Endang; Atmapratiwi, Heppy; Mayasari, Ira (Presisi Jurnal Pengabdian Masyarakat, 2023)
This Indonesian Language Training for Basic Level Foreign Speakers was attended by Thai residents, which was coordinated by the Faculty of Liberal Arts, Maejo University, Thailand. The purpose of this activity is for BIPA participants from Thailand to know and understand Indonesian. This activity teaches Indonesian from the basics to the participants. BIPA teaching cannot be separated from four aspects of language skills, namely listening, speaking, reading, and writing skills. This activity is intended for participants from Thailand who have different backgrounds. Most of the participants have never received BIPA training. The positive effect of this activity is that BIPA participants can understand and master Indonesian from a basic level which can be applied when visiting Indonesia. In addition, the BIPA participants were also taught the culture in Indonesia so that they would be more familiar with the culture and traditions that exist in Indonesia.